Entrepreneurship Educational Offerings: An Examination of Module Design and Its Challenges - Alakaleek , Wejdan; Harb , Yousra; Harb, Ayman; Al-Maaitah, Hadeel (Jordan Journal of Business Administration, 2025)
This study aims to examine the state of entrepreneurship educational offerings within Jordanian universities. First, it investigates the relationships between the main elements of entrepreneurship module design (module content, pedagogy, audience and educators’ characteristics). Second, the study explores some factors that shape entrepreneurship module design. Both quantitative and qualitative methods were utilised to collect the data from entrepreneurship module educators. The research findings concluded that the educational offerings are characterized by focusing on the theoretical side of entrepreneurship and the high usage of traditional teaching methods. The university educational system (grading system, number of students, and support for curriculum activities) and educators’ experiences (entrepreneurship teaching and research background and design of a practically-based curriculum) are among the main challenges encountered by Jordanian entrepreneurship educators. The study’s findings provide insights for stakeholders to make better-informed decisions in relation to the entrepreneurship educational offerings.